Evaluating, taxing and insuring agricultural enterprises - Cicero I. Limberea (IBSU Scientific Journal (IBSUSJ), 2011)
By analyzing the pros and cons of the US farms taxation methodologies, this paper aims to suggest that best practice of taxing farms in transition economies would be consistent with a multiple of cash flow valuation approach and suggests that a liquid market for agricultural insurance can be created in emerging economies as it provides a methodology for valuation of drought insurance contracts. As such recent drought and flood damages in such countries could have been reimbursed privately and thus the recent rise of food prices internationally may have been prevented.
Keywords: H21; Q12; Q14; 330; evaluation; taxing; insurance; agriculture; US farms